Key techniques of reservoir engineering and injection–production process for CO2 flooding in China's SINOPEC Shengli Oilfield. (September 2015) - Lv, Guangzhong; Li, Qi; Wang, Shijie; Li, Xiaying
Abstract: This paper addresses the geological problems and engineering hot points of the CO2 flooding, such as the big vertical span of the beach-bar sand, the strong reservoir heterogeneity, the distribution of residual oil, and the problem of gas channeling. The core identification, log analysis, seismic interpretation, laboratory test and numerical simulation of reservoir engineering are integrated to investigate the geological characteristics of the reservoir in the demonstration zone of SINOPEC Shengli Oilfield. It demonstrates the reservoir is large but it has thin thickness, low porosity and super-low permeability. Due to some great differences between the beach sand and the bar sand, the oil reservoirs of demonstration zone are divided into 2 sand groups, 8 small layers, and 17 sand bodies in total. Then, a 3D geological model and qualitative evaluation system of safety of vertical faults are built. The optimal evaluation method of CO2 flooding and sequestration is established. According to the engineering optimization of the CO2 flooding, the results of a recommendation scheme indicate that the enhance oil recovery can increase by 6.7%, the total injection volume is expected to reach to 563 × 10 4  t, and CO2 sequestration rate is 60.5%. Finally, the multi-level umbrella downhole gas separator is designed, and the high gas–oil ratio (GOR) production string and free kill gas injection string are also successfully developed for the CO2 -EOR.